Pemanfaatan Aplikasi Zoom Meeting dalam Proses Pembelajaran di Masa Pandemi Covid-19 pada Mahasiswa Jurusan Pendidikan IPS FKIP Universitas Tadulako - Abdul Hamid (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2020)
During the Covid-19 pandemic, Tadulako University conducted a distance learning system. Familiar and widely used applications in remote learning using media or zoom meeting apps. The purpose of this research was to find out the use of Zoom Meeting application against students of ips education department of FKIP Tadulako University, during the Covid-19 pandemic. This research uses qualitative methods and uses grounded theory methods. The data collection technique was conducted with interviews on 32 students of the Faculty of Education Department of Tadulako University. The results of this study, show that the utilization of Zoom Meeting application is quite effective for students of tadulako university geography education program. However, the Zoom Meeting application is better because in the Zoom Meeting application communication between individuals is done orally compared to the utilization of learning that conducts communication activities in writing according to educational communication theory.